2006
DOI: 10.2174/157016206776055093
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Restriction Factors In Mammalian Cells - An Ancient Defense System Finds A Modern Foe

Abstract: Cross-species transmission of retroviruses poses a threat to mammalian species. Zoonoses have given rise to devastating diseases because the host organism is not prepared to resist a new pathogen. Mammals have developed several layers of defense against viruses, including an intracellular antiretroviral defense, a part of innate immunity. Retroviral restrictions had been studied for decades using murine leukemia virus in mice, however it has become clear that primates too have intrinsic mechanisms to ward off … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 347 publications
(557 reference statements)
0
18
0
Order By: Relevance
“…5 It has been shown that the propagation of human immunodeficiency virus 1 (HIV-1) strains lacking the accessory protein vif (virion infectivity factor) is suppressed in a number of nonpermissive cells and that this block is due to the expression of the cytidine deaminase APOBEC3G (A3G). [6][7][8] Further studies have revealed that A3G induces massive C-to-U deamination of single-stranded retroviral DNA, which may result in the reduced accumulation of viral reverse transcripts and/or lethal G-to-A hypermutation.…”
Section: H Epatitis B Virus (Hbv)mentioning
confidence: 99%
See 1 more Smart Citation
“…5 It has been shown that the propagation of human immunodeficiency virus 1 (HIV-1) strains lacking the accessory protein vif (virion infectivity factor) is suppressed in a number of nonpermissive cells and that this block is due to the expression of the cytidine deaminase APOBEC3G (A3G). [6][7][8] Further studies have revealed that A3G induces massive C-to-U deamination of single-stranded retroviral DNA, which may result in the reduced accumulation of viral reverse transcripts and/or lethal G-to-A hypermutation.…”
Section: H Epatitis B Virus (Hbv)mentioning
confidence: 99%
“…17 APOBEC3C (A3C) is another member of the APO-BEC family. 5,19 Unlike the larger A3G protein containing 2 deaminase domains, the smaller A3C protein contains a single deaminase domain. The impact of A3C on the HBV life cycle is poorly understood.…”
Section: H Epatitis B Virus (Hbv)mentioning
confidence: 99%
“…(2); integration of the cDNA into the host genome (3); transcription of the provirus by RNA polymerase II (4); translation of viral mRNA (5); viral core particle assembly, which includes encapsidation of viral mRNA (6); and viral-particle exit (7). The stages of retrotransposon replication include transcription of a genomic element by RNA polymerase II (4), translation of retrotransposon mRNA (5), virus-like particle assembly and packaging of the retrotransposon mRNA (6), reverse transcription of retroelement RNA to form a linear double-stranded cDNA (2), and insertion of cDNA into the genome by integration or homologous recombination with preexisting retrotransposons or solo LTRs in the genome (3).…”
Section: Genome-wide Screens In Yeast: Different Screens Different Gmentioning
confidence: 99%
“…Assaf sheep are raised in intensive conditions and show very high VMV seroprevalences, while Latxa are kept in semi-intensive conditions and have low-medium infection levels. The extremely elevated seroprevalence and disease levels observed in the Assaf breed (Leginagoikoa et al, 2010) may render A3 proteins unable to counteract VMV infection, since high-titer infections may saturate these cellular factors (Baumann, 2006;Münk et al, 2010). The low frequency of one of the alleles conditions the statistical analysis; this problem should be addressed by increasing the sample size.…”
Section: Discussionmentioning
confidence: 99%